Politik Hukum Pembentukan Pasal 20 Undang-Undang tentang Paten di Indonesia dalam Perspektif Hak Kekayaan Intelektual - Raden Ani Eko Wahyuni; Muhammad Zainuddin (Journal of Judicial Review, 2021)
Patents as part of intellectual property rights that form the basis of modern industrial growth are based on new inventions, sophisticated technology, high quality, and quality standards. A patent is granted to protect the invention in the field of technology. Provisions in Law Number 13 of 2016 regarding Patents are considered by some to have made it difficult for patent holders from abroad to take part in Indonesia. The research method used in this study is normative juridical aiming to investigate patent issues from the perspective of the law governing it, in this case about the reasons underlying its formation, namely in Article 20 of the intellectual property rights perspective. Based on the research that has been done, the enactment of Article 20 of Law Number 13 of 2016 concerning Patents is expected that the Indonesian people will feel better welfare and life because it is expected that there will be many foreign investors registering their patents in Indonesia in addition to absorbing technology transfers and opening up many employment which will then result in reduced unemployment.